Airway remodeling in chronic obstructive pulmonary disease: characteristics and opportunities - Pan, Minjie; Zhou, Xiaojing (Frontiers in Medicine, 2025)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease characterized by irreversible airway remodeling and is a global burden on the healthcare system. The World Health Organization predicts it will be the third leading cause of death by 2030. The causes of airway remodeling in COPD are complex. Several elements, such as the lung parenchyma and interstitium, as well as endothelium, mesenchymal cells, and a range of bioactive chemicals, work together to either encourage or impede the alteration of the airway’s structure during the remodeling process. Airway remodeling is an important factor in the irreversible limitation of ventilatory function. To reduce airway remodeling, significant efforts are being directed to find effective therapeutic ways that inhibit airway remodeling. In China, many patients use traditional Chinese medicine (TCM). Some TCM can improve the symptoms and lung function of COPD patients. Here, we describe the molecular mechanisms and key cellular players of airway remodeling in COPD patients and review the Chinese herbal medicines that may effectively inhibit airway remodeling.